DENSITY OF NERITIDAE IN THE COASTAL WATERS OF SERI VILLAGE, AMBON CITY - Langkode, Servin; Leiwakabessy, Fredy; Salmanu, Sriyanti Imelda Aksamina (Universitas Pattimura, 2022)
These marine natural resources include various types of fish, molluscs, and crustaceans. Maluku is a waters rich in benthic organisms, the coastal environment of Seri village can be said to be productive which shows various types of resources that can be utilized continuously in the presence of various types of marine organisms or marine biota such as Nerita. This research is a form of scientific contribution to learning marine biology. This research is a descriptive type of research, to describe or describe information about the density of Neritidae in the coastal waters of Seri Village which is made in the form of tables and figures. The results of the calculation of the density of Neritidae in the coastal waters of Desa Seri which were carried out as a whole from 3 transects found 7 species, 1 family, 1 genus and 207 individuals in the phylum Mollusca. By calculating the density on the coast of Seri Village, the values ​​for each species are as follows: Nerita squamulata is 0.001833, Nerita chamaeleon is 0.002167, Nerita maxima is 0.002167, Nerita polita is 0.026333, Nerita albicilla is 0, 0015, Nerita planospira was 0.000333 and Nerita patula was 0.000167 with a total absolute density of 0.0345. according to the density category according to Cox (1967) which explains that 0 = no density, 1-10 = less density, 10-20 = sufficient density and > 20 = very high density, thus it can be concluded that Neritidae in coastal waters of Seri village is no density.